2017
DOI: 10.3892/etm.2017.5147
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of resveratrol on osteoporosis via activation of the SIRT1‑NF‑κB signaling pathway in rats

Abstract: Abstract. The aim of the present study was to determine the protective effects of resveratrol on a rat model of osteoporosis and examine the associated mechanisms of its action. Rats were randomized into the following groups: Control, osteoporosis, osteoporosis + low-dose resveratrol, osteoporosis + middle-dose resveratrol and osteoporosis + high-dose resveratrol groups. Resveratrol treatment was administered 7 days after surgery for 8 weeks. ELISA assay was used to analyze alkaline phosphatase (ALP) and osteo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(54 citation statements)
references
References 34 publications
(41 reference statements)
4
50
0
Order By: Relevance
“…The OVX rats presented bone loss and weight gain. In addition, the resveratrol treatment alleviated osteoporosis symptoms, which were in agreement with other publications [32,33].…”
Section: Discussionsupporting
confidence: 92%
“…The OVX rats presented bone loss and weight gain. In addition, the resveratrol treatment alleviated osteoporosis symptoms, which were in agreement with other publications [32,33].…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with our findings that NO‐releasing compounds stimulate osteoblast differentiation and bone formation, NO‐donors also antagonize ovariectomy‐ or corticosteroid‐induced bone loss in rodents (Wimalawansa et al ., ; Hukkanen et al ., ) and improve fracture healing (Corbett et al ., ; Diwan et al ., ). Similarly, recent work suggests RSV might also be protective in an experimental model of osteoporosis in rats (Wang et al ., ), supporting our hypothesis that RSV might increase overall bone mass under normal conditions. However, whether such findings are truly translatable to human physiology remain to be determined where for example bioavailability of RSV and lifestyle factors may enhance or diminish the effects observed in rodent models (Tome‐Carneiro et al ., ; Berman et al ., ).…”
Section: Discussionsupporting
confidence: 89%
“…RSV promotes osteoblast differentiation from mesenchymal stem cells in vitro (Zhou et al ., ; Kupisiewicz et al ., ; Shakibaei et al ., ), reduces the formation of bone‐resorbing osteoclasts (Shakibaei et al ., ) and may be protective in an experimental model of accelerated bone disease (Wang et al ., ) suggesting that RSV supplementation may be beneficial for bone health to prevent the age‐related decline in functional integrity or as an experimental medicine in disorders of excessive bone destruction. However, the intracellular mechanisms activated by RSV stimulation remain complex and convoluted.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have indicated the beneficial effects of sirtuins as the best small molecule that activate sirtuins, which extended lifespan in a yeast model [104][105][106][107][108][109]. Although only the longevity extension effect of resveratrol has been reported in C. elegans and D. melanogaster, many subsequent studies reported that resveratrol intake promotes health and plays a preventive role in age-related diseases, such as cancer [110][111][112][113], atherosclerosis [114,115], arthritis [116,117], cataract [118][119][120], cardiovascular disease [121], hypertension [122,123], type 2 diabetes [124][125][126][127], osteoporosis [128][129][130], and Alzheimer disease [131][132][133]. In clinical studies, resveratrol intake improved the memory capacity of elderly individuals and reduced blood lipid levels in obese and type 2 diabetic patients [134,135].…”
Section: Resveratrolmentioning
confidence: 99%